BLURRING THE BOUNDARIES: DEVELOPING PEDAGOGICAL SKILLS OF TEACHERS IN THE ERA OF MEDIATOCRE EDUCATION (American Journal of Pedagogical and Educational Research, 2024)
This article discusses the concept of "mediatocre education," which refers to an educational approach that heavily relies on digital media and technology for instructional purposes. The author explores the challenges faced by teachers in adapting to this evolving landscape and offers insights into how they can enhance their pedagogical skills to thrive in the mediatocre era.The article highlights three key challenges faced by teachers in a mediatocre education system: technological competence, pedagogical adaptation, and media literacy. It emphasizes the need for teachers to develop proficiency in using technology effectively, adapt their pedagogical strategies to online and blended learning environments, and acquire media literacy skills to critically evaluate and curate digital content. To address these challenges, the author suggests several strategies for enhancing pedagogical skills in the mediatocre era. These strategies include continuous professional development, collaboration and peer learning, reflective practice, student-centered approaches, and integrating media literacy education into the curriculum. The article argues that by embracing these strategies, teachers can navigate the new educational paradigm effectively and create engaging and transformative learning experiences for their students.